Pronounced thrombocytosis in transgenic mice expressing reduced levels of Mpl in platelets and terminally differentiated megakaryocytes - Tiedt, Ralph; Coers, Jörn; Ziegler, Sandra; Wiestner, Adrian; Hao-Shen, Hui; Bornmann, Caroline; Schenkel, Johannes; Karakhanova, Svetlana; Sauvage, Frederic J.; Jackson, Carl W.; Skoda, Radek Ctirad (Blood, 2009)
We generated mice expressing a full-length Mpl transgene under the control of a 2-kb Mpl promoter in an Mpl−/− background, effectively obtaining mice that express full-length Mpl in the absence of other Mpl isoforms. These mice developed thrombocytosis with platelet levels approximately 5-fold higher than wild-type controls and markedly increased megakaryocyte numbers. The reintroduction of one wild-type Mpl allele restored normal platelet counts. We excluded the deletion of Mpl-tr, a dominant-negative isoform, as the underlying molecular cause for thrombocytosis. Instead, we found that transgene expression driven by the 2-kb Mpl promoter fragment was decreased during late megakaryocyte maturation, resulting in strongly diminished Mpl protein expression in platelets. Because platelets exert a negative feedback on thrombopoiesis by binding and consuming Tpo in the circulation through Mpl, we propose that the severe reduction of Mpl protein in platelets in Mpl-transgenic Mpl−/− mice shifts the equilibrium of this feedback loop, resulting in markedly elevated levels of megakaryocytes and platelets at steady state. Although the mechanism causing decreased expression of Mpl protein in platelets from patients with myeloproliferative disorders differs from this transgenic model, our results suggest that lowering Mpl protein in platelets could contribute to raising the platelet count.